Frequency plan optimization based on genetic algorithms for cellular networks - Megnafi, Hicham (Array, 2020)
Cellular networks are constantly evolving to ensure a better Quality of Service (QoS) and quality of coverage ever more important. The radio cellular systems are based on frequency allocation. In this context, frequency allocation principle consists in choosing an optimal frequency plan to meet traffic demand constraints and communication quality while minimizing the radio interferences. This paper proposes an optimal frequency allocation approach based on genetic algorithms to minimize co-channel and adjacent channel interference. The validation of this new approach is conﬁrmed by the results of the work we have done in the GSM network. In fact, we used the ﬁle obtained by the OMC-R, which deﬁnes the adjacent cells of each cell and the frequencies allocated to the considered area. The results obtained clearly show the effectiveness and robustness of the approach used.